PEMANFAATAN LINGKUNGAN SEBAGAI SUMBER BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Wuryandani, Wuri (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Civics Education in elementary school is a subject full of affective domain. To develop student's affective attitudes, the learning process not only based on text book, but also from environment. The learning experience obtained as much as possible to provide real learning experiences of students. One of source which can be utilized in Civic Education learning is based on the environment. Environment that can be used for Civic Education learning in primary schools is the natural environment, social environment, and cultural environments.